NADPH-dependent ROS accumulation contributes to the impaired osteogenic differentiation of periodontal ligament stem cells under high glucose conditions - Zhang, Yi-lin; An, Ying; Sun, Li-Juan; Qu, Hong-Lei; Li, Xuan; He, Xiao-Tao; Wu, Rui-Xin; Chen, Fa-Ming; Tian, Bei-Min; Yin, Yuan (Frontiers in Endocrinology, 2023)
Diabetes mellitus is an established risk factor for periodontal disease that can aggravate the severity of periodontal inflammation and accelerate periodontal destruction. The chronic high glucose condition is a hallmark of diabetes-related pathogenesis, and has been demonstrated to impair the osteogenic differentiation of periodontal ligament stem cells (PDLSCs), leading to delayed recovery of periodontal defects in diabetic patients. Reactive oxygen species (ROS) are small molecules that can influence cell fate determination and the direction of cell differentiation. Although excessive accumulation of ROS has been found to be associated with high glucose-induced cell damage, the underlying mechanisms remain unclear. Nicotinamide adenine dinucleotide phosphate (NADPH) is an important electron donor and functions as a critical ROS scavenger in antioxidant systems. It has been identified as a key mediator of various biological processes, including energy metabolism and cell differentiation. However, whether NADPH is involved in the dysregulation of ROS and further compromise of PDLSC osteogenic differentiation under high glucose conditions is still not known. In the present study, we found that PDLSCs incubated under high glucose conditions showed impaired osteogenic differentiation, excessive ROS accumulation and increased NADPH production. Furthermore, after inhibiting the synthesis of NADPH, the osteogenic differentiation of PDLSCs was significantly enhanced, accompanied by reduced cellular ROS accumulation. Our findings demonstrated the crucial role of NADPH in regulating cellular osteogenic differentiation under high glucose conditions and suggested a new target for rescuing high glucose-induced cell dysfunction and promoting tissue regeneration in the future.